Identifying key environmental indicators in the assessment of the proof-of-concept in pigment production from the marine Cyanobacterium cyanobium sp. - Pagels, Fernando (2022)
Cyanobacteria have long attracted market interest as a source of natural compounds such as pigments with proven bioactivity (carotenoid and phycobiliproteins). The cultivation and extraction processes for such compounds have been developed at different levels, from laboratory trials to photobioreactors on a demonstration scale. Based on this experience, it is possible to propose how the different stages of the process can be improved based on environmental performance indicators. The Life Cycle Assessment (LCA) methodology allows to identify the hotspots that represent the greatest environmental impacts and to propose strategies to focus on those stages that can be improved. The general environmental indicators have been identified and the results showed that cyanobacteria cultivation has the greatest influence on environmental impact for all scales considered (from 20 L to 100 m3), which is attributed to the energy requirements. The main changes proposed to reduce the impact should focus on the stages of reactor cleaning, culture medium sterilisation and biomass drying. The implementation of these improvement alternatives can reduce the impact of the production and extraction processes by 85%. This work demonstrates how technological development must go hand in hand with impact assessment to make the best decisions in the overall process.